Standardization of molecular monitoring of CML: results and recommendations from the European treatment and outcome study: chronic myologenous leukemia - White, Helen; Salmon, Matthew; Albano, Francesco; Andersen, Christina Søs Auður; Balabanov, Stefan; Balatzenko, Gueorgui; Barbany, Gisela; Cayuela, Jean-Michel; Cerveira, Nuno; Cochaux, Pascale; Colomer, Dolors; Coriu, Daniel; et al. (Leukemia, 2022)
Standardized monitoring of BCR::ABL1 mRNA levels is essential for the management of chronic myeloid leukemia (CML) patients. From 2016 to 2021 the European Treatment and Outcome Study for CML (EUTOS) explored the use of secondary, lyophilized cell-based BCR::ABL1 reference panels traceable to the World Health Organization primary reference material to standardize and validate local laboratory tests. Panels were used to assign and validate conversion factors (CFs) to the International Scale and assess the ability of laboratories to assess deep molecular response (DMR). The study also explored aspects of internal quality control. The percentage of EUTOS reference laboratories (n = 50) with CFs validated as optimal or satisfactory increased from 67.5% to 97.6% and 36.4% to 91.7% for ABL1 and GUSB, respectively, during the study period and 98% of laboratories were able to detect MR4.5 in most samples. Laboratories with unvalidated CFs had a higher coefficient of variation for BCR::ABL1IS and some laboratories had a limit of blank greater than zero which could affect the accurate reporting of DMR. Our study indicates that secondary reference panels can be used effectively to obtain and validate CFs in a manner equivalent to sample exchange and can also be used to monitor additional aspects of quality assurance.
Gesehen am 02.01.2024